Pola Aktivitas Orangutan Sumatera (Pongo abelii) Pada Struktur dan Komposisi Vegetasi Hutan di Pusat Pengamatan Orangutan Sumatera Taman Nasional Gunung Leuser (Activity pattern of Sumatran Orangutan (Pongo abelii) in the Structure and Composition of For - Reza Rangkuti; Pindi Patana; Siti Latifah (Program studi Kehutanan USU, 2013)
Forest act as a habitat which is one of the main elemen in orangutan lives. Increasing rate of forest degradation in recent years considerable influence on the orangutan population growth, its looks from the orangutan population decline significantly in recent years. Therefore, it is necessary to the preservation of orangutans through habitat management, and ecological and quantitative aspect of orangutan become interest of this study. The methodology which used in this research are the direct observation of daily activities orangutan’s and vegetation analysis in the forest spots that have been passed by the orangutan. The result of this research shows that orangutan average active starting at 07.33 WIB and start to make a nest for sleep approximately at 18.15 WIB with an average length of daily activity orangutan approximately 10 hours 42 minutes. Daily activity averange of orangutan for proportion duration are 15,03% for feeding, 36,59% for moving, 44,82 % for resting, and 3,56% for nesting and for frequencies are 24,09% for feeding, 32,95% for moving, 37,76% for resting, and 5,2%% for nesting. The composition of forest vegetation consists of 24 species of trees, 15 species of poles, and 20 species of saplings which identified overall approximately 88,53% of food plants. PPOS forest area has an index of species diversity (Sannon Wiener index) 2.717 species of trees, 2,235 species of poles, and 2,554 species of saplings. Keywords: Sumatran Orangutan, Population, Structure and composition of forest vegetation, Sumatran Orangutan Observation Center Gunung Leuser National Park